Entomopathogenic Fungi: Dual Role in Insect Control and Plant Disease Management - Yadav, Sunita; Thodusu, Mamatha; Shankar, Uma; Nautiyal, Anchala; Khajuria, Marvi; Sarangi, Satyabrata; Maheshwari, Sourabh; Pandey, Kartikey (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Entomopathogenic fungi (EPF) are important biological agents in modern agriculture, offering eco-friendly solutions for integrated pest and disease management. With their dual functionality, EPF target a wide range of insect pests while suppressing plant pathogens, presenting a sustainable alternative to synthetic pesticides. The biology, mechanisms, and applications of EPF, highlighting their ability to parasitize insects through adhesion, enzymatic penetration, and toxin production while simultaneously managing plant pathogens via antibiosis, competition, systemic resistance induction, and direct parasitism. Advances in genomics have unveiled molecular insights into EPF pathogenicity, paving the way for biotechnological enhancements, including genetically engineered strains with improved efficacy, thermal tolerance, and host specificity. Innovative formulation technologies, such as nano-carriers and microencapsulation, have enhanced the viability and precision delivery of EPF, improving field efficacy. The integration of EPF with precision agriculture tools, including drones and sensor-based systems, allows targeted applications and data-driven pest management. Their compatibility with organic farming systems underscores their role in fostering sustainable and environmentally conscious agricultural practices. Despite these advancements, challenges remain, including environmental limitations, production costs, regulatory hurdles, and potential non-target effects. Addressing these challenges through interdisciplinary research and stakeholder education is critical for maximizing EPF's potential. As agriculture faces mounting pressures from climate change, pest resistance, and ecological degradation, EPF stand as a promising solution, contributing to soil health, biodiversity conservation, and reduced chemical dependency. The importance of EPF in shaping resilient agroecosystems, driving the transition toward sustainable agriculture while ensuring food security and environmental sustainability. The integration of cutting-edge technologies and policy support will be important in scaling the adoption of EPF-based solutions, positioning these fungi as a cornerstone in the future of agricultural innovation and sustainability.